Hakikat an-Nas dan Ummah Dalam Al-Qur’an: Telaah Perspektif Pendidikan Islam - Lola Fadilah; Satria Kharimul Qolbi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Nature of an-Nas and Ummah in the Qur'an: Studying the Perspective of Islamic EducationHumans are creatures created by Allah SWT who have complicated devices in their creation, this is of course a form of perfection from humans, it is necessary to have a review from humans themselves. This research is a literature study with a qualitative approach and uses the maudlu'i interpretation method with a thematic interpretation approach. The essence of An-Nas with all its elements, starting from physical needs, lust, and reason, there must be a balance between these elements. The essence of the ummah which means that humans are created to have diversity is not created in one ummah, but this diversity has the same goal. The result of the discussion is that human beings are essentially created to serve as caliphs and as people to carry out Allah's commands and stay away from His prohibitions. In the perspective of education, the existence of human groups emphasizes that it can give birth to a good legacy from each generation's journey